The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5117/nedlet2016.2.grut
|View full text |Cite
|
Sign up to set email alerts
|

Nederland en de Nobelprijs voor literatuur 1901-1965

Abstract: Dutch literature and the Nobel Prize 1901-1965Since 1901 no Dutch language author has won the Nobel Prize for literature, which is surprising for a language of 22 million speakers. In how far is it possible to explain this? Whereas much research on the prize is about rumours and guessing on poetics, this article turns towards sources that have not been used systematically before: the nomination database 1901-1964 of the Nobel Prize Organisation, recently updated with the year 1965. The article first reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…indicated that he was a member of the Royal College of Surgeons (England) and a Licentiate of the Royal College of Physicians of England. Medicine was not a focus in the nominations for the Dutch physician Simon Vestdijk either [ 24 ]. Other nominators emphasized that the works by the nominee in question were closely intertwined with medicine, as was the case with Gottfried Benn and Hans Carossa.…”
Section: Discussion: All Nobel Laureates Are Alike; Each Unhappy Nomimentioning
confidence: 99%
“…indicated that he was a member of the Royal College of Surgeons (England) and a Licentiate of the Royal College of Physicians of England. Medicine was not a focus in the nominations for the Dutch physician Simon Vestdijk either [ 24 ]. Other nominators emphasized that the works by the nominee in question were closely intertwined with medicine, as was the case with Gottfried Benn and Hans Carossa.…”
Section: Discussion: All Nobel Laureates Are Alike; Each Unhappy Nomimentioning
confidence: 99%